Sistem Penilaian Kinerja Pegawai Menggunakan Logika Fuzzy (Studi Kasus PT. PLN Persero APD Bali) - M.A. Ineke Pakereng, Ni Made Grace Advendi, Andeka Rocky Tanamaah, (SMATIKA, 2012)
This research is about the employeeâs working perf ormance evaluation system in PT. PLN Persero APD Bali which uses fuzzy logic. This system was built to help the company in evaluating its employeeâs working performance which previously done manually. The fuzzy logic method application in employeeâs working performance evaluation will help improving the process to evaluate due to its compilation of limits that function as parameter and criteria in evaluating the employee and their competencies. The result of this evaluation is levels of improving employeeâs competencies and careers that help the company in developing the employeeâs career.